Phase I trial of low dose decitabine targeting DNA hypermethylation in patients with chronic lymphocytic leukemia and non-Hodgkin’s lymphoma: Dose-limiting myelosuppression without evidence of DNA hypomethylation - Blum, Kristie A. (2010)
PURPOSE: Targeting aberrant DNA hypermethylation in chronic lymphocytic leukemia (CLL) and non-Hodgkin’s lymphoma (NHL) with decitabine may reverse epigenetic silencing in B-cell malignancies. METHODS: Twenty patients were enrolled in two phase I trials to determine the minimum effective pharmacologic dose (MEPD) of decitabine in patients with relapsed/refractory CLL (n=16) and NHL (n=4). RESULTS: Patients received 1–3 cycles of decitabine. Dose limiting toxicity (DLT) was observed in 2 of 4 CLL and 2 of 2 NHL patients receiving decitabine at 15 mg/m(2)/d days 1–10, consisting of grade 3–4 thrombocytopenia and hyperbilirubinemia. Six patients with CLL received decitabine at 10 mg/m(2)/d days 1–10 without DLT; however, re-expression of methylated genes or changes in global DNA methylation were not observed. Therefore, a 5-day decitabine schedule was examined. With 15 mg/m(2)/d decitabine days 1–5, DLT occurred in 2 of 6 CLL and 2 of 2 NHL patients, consisting of grade 3–4 neutropenia, thrombocytopenia, and febrile neutropenia. Eight patients had stable disease. In 17 patients, there were no significant changes in genome-wide methylation or in target gene re-expression. CONCLUSION: Dose-limiting myelosuppression and infectious complications prevents dose escalation of decitabine to levels associated with changes in global methylation or gene re-expression in CLL and NHL.